The math inspectors : The case of the Claymore diamond - Kenney, Daniel; Boever, Emily ([Clemmons, N.C.] : Bakken Books, 2015)
"When the Claymore diamond is stolen from Ravensburg's finest jewelry store, Stanley Carusoe gets the bright idea that he and his friends should start a detective agency"--Back cover.
3-6
3-6
English.
Keywords: Child detectives -- Juvenile fiction; Mathematics -- Juvenile fiction; Child detectives -- Fiction; Mathematics -- Fiction; Mystery and detective stories; Children -- Fiction; Detectives -- Fiction; Mathematics -- Fiction; Mystery fiction; Detective and mystery fiction; Mathematical fiction